The Role of Traditional Kyai in Mitigating Early Marriage in Indonesia: An Analysis of a Social Phenomenon within the Maslahah Framework - Masiroh, Siti; Harisudin, M. Noor; Ridlo, Mokhamad Ali (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
Early marriage is currently a significant concern in developing countries, such as Indonesia. Attention has been directed towards the causes and effects of the high prevalence of early marriage. Various government agencies, community leaders, traditional leaders, and religious leaders have implemented efforts to prevent early marriage; however, these initiatives have not succeeded in significantly reducing its incidence. This study examines the social phenomenon of a Kyai in Lamongan Regency, East Java Province, Indonesia, who plays a pivotal role as a religious figure in the prevention of early marriage. This research adopts a qualitative methodology employing field research methods. Primary data sources were obtained from relevant agencies in Lamongan Regency, the Kyai as an actor, santri (Islamic students), parents of santri, and the broader community. Data collection was conducted through structured interviews, participatory observation, and documentation. The research data were subsequently analysed using functional structure theory and Islamic law, particularly focusing on the aspect of maslahah (public interest). The findings of this study indicate that the role of the Kyai as educators and charismatic religious figures has positively impacted the reduction of early marriage rates in Lamongan. Furthermore, the social role of the Kyai is inextricably linked to their position as figures who encourage the community to foster a conducive environment for the development of the younger generation. The strategies devised by the Kyai include the design of a curriculum that encompasses material on marriage, the provision of guidance to the guardians of Islamic boarding school students, and the organisation of religious lectures for the general public. This study presents a functional structure model that operates effectively and advocates for local governments to optimise the role and function of the Kyai in the prevention of early marriage in Indonesia.